Owner liability and financial reporting information as predictors of firm default in bank loans - Bhimani, A.; Gulamhussen, M. A.; Lopes, S. R. (Review of Accounting Studies, 2014)
We examine the effects of owner liability and non-accounting and financial accounting information on the probability of default as defined in Basel II in bank loan contracted by non listed firms. We model default as a function of owner liability and accounting and non-accounting information of non-listed firms, drawing on 43,117 annual accounts of 16,029 firms over a 7-year period. Our estimations based on mixed logistic regressions with random parameters show that the predicted default probability of full-liability firms is 0.72 times that of limited liability firms. The likelihood ratio test for omitted variables confirms the additional predictive ability of liability status over and above other non-accounting and financial accounting information. A Heckman self-selection model does not indicate sampling bias. The particular definition of default used in the study enables the findings to be generalizable across other institutional contexts.